UJI ABB INDEKS STABILITAS TOTAL-TOTAL DALAM PENERAPAN BAHAN PREDIKTOR KEJADIAN CUMULONIMBUS DAN THUNDERSTORM DI PANGKALPINANG - Fadel Muhammad Madjid; Antika Heni Hestiwi; Putri Santy Siregar (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Atmospheric stability condition is needed to be noticed in a weather forecast especially for short range forecasting. Stability index can be used as a reference to determine future conditions about the exitence of thunderstorm and Cumulonimbus clouds. But the old Total-Totals (TT)  threshold is still considered unsuitable for Pangkalpinang. This study uses Total-Totals Index from January to December at 2012-2015 to get the recent Total-Totals (TT) threshold using statistic calculation. After the recent Total-Totals (TT) threshold was obtained, performance test is done for Januari to December 2016. Thunderstorm could already happen when the Total Totals(TT) Index is TT >= 37,76. Based on contingency tabel, miss condition on recent Total-Totals (TT) threshold  less than the old Total-Totals (TT) threshold . In reverse with the hit condition. Probability of Cb and TS that could be detected by recent. Total-Totals (TT) threshold is  better than the old Total-Totals (TT)  threshold. The accuration of recent  Total-Totals (TT) threshold is better during the day than during the night. It can be concluded that recent  Total-Totals (TT) threshold is able to improve sensitivity on detecting existence of CB and TS.Keywords: Total-Totals, Threshold, CB, TS